FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK HOTEL - Septiana Dewi, Putu; Sukartha, I Made (E-Jurnal Akuntansi, 2015)
Taxes as a source of revenue has a very large role in financing national development. This study aims to determine the effect of taxpayer awareness, quality of service, moral obligation, tax penalties, and tax audits on tax compliance in paying taxes hotels in Denpasar City Revenue Service. Sampling method accidental sampling technique. The respondents in this research were 100 taxpayers hotels obtained by the formula Slovin. This study tested using multiple linear regression analysis with SPSS 15:00 for windows. Based on the results of the analysis can be concluded that the taxpayer awareness variables, quality of service, moral obligation, tax penalties, and tax audits positive effect on tax compliance in paying taxes hotels in Denpasar City Revenue Service.
Keywords: Taxpayer Awareness, Service Quality, Moral Obligations, Tax Penalties, Tax Audit, Compliance Taxpayer